Assessing Foodservice Personnel’s Knowledge, Attitude and Practices in IDDSI Pureed Diet Preparation in Malaysia - Hui Yan Ngae; Ahmad Riduan Bahauddin; Aizul Azri Azizan (Quantum Academic Publisher Enterprise, 2026)
Indexed by MyCite